Non-governmental organizations and development - Lewis, David (Routledge perspectives on development, 2009)
A concise, comprehensive and critical introduction to the subject of Non-Governmental Organizations (NGOs) and development. This critical overview will be useful to students of development studies at undergraduate and masters levels, as well as to more general readers and practitioners